Assessment of regional and global climate models for the investigation of monsoon rainfall variability over the North‐West Himalayan region. (28th December 2021) - Kundu, Sudip Kumar; Singh, Charu; Chauhan, Prakash
Abstract: Present study is an attempt to evaluate the rainfall pattern obtained from the selected Regional Climate Models (RCMs) which participated in Coordinated Regional Climate Downscaling Experiment for the South Asia region (CORDEX‐SA) and the Global Climate Models (GCMs) which participated in Coupled Model Intercomparison Project Phase 5 (CMIP5) with respect to the high‐resolution ground‐based Indian Meteorological Department (IMD) rainfall data during the principal monsoon season (i.e., June 1 to September 30) from 1976 to 2000 over the states of Himachal Pradesh (HP) and Uttarakhand (UK) in North‐West Himalayan Region (NWH). Considering the inter‐model differences, the multimodel means (MMM) of both of the CORDEX‐SA and CMIP5 models have been compared with the IMD gridded rainfall data set so as to find out the suitable set of models (whether CORDEX‐SA or CMIP5) for assessing the rainfall variability over this region. The CORDEX‐MMM indicates a poor relationship with IMD data compared with the CMIP5‐MMM over both the NWH states of HP and UK. CMIP5‐MMM demonstrates better ability to represent extreme rainfall events as compared with the CORDEX‐MMM. Significant bias has been noted for both of the CORDEX‐MMM and CMIP5‐MMM with respect to the IMD data sets, nevertheless, differences were found to be minimal in case of CMIP5‐MMM in comparison to CORDEX‐MMM. In case of the simulated rainfall from CMIP5‐MMM over both HP and UK regions, RMSE, MAE and bias, all are much smaller than that of the CORDEX‐MMM simulations with respect to the IMD rainfall data. Further to this, CMIP5‐MMM notably performs better in case of delineating extreme cases of inter‐annual variability except CORDEX‐MMM for the state of UK. Results presented here encompass the entire spectrum of summer monsoon rainfall variability, for example, daily, monthly, seasonal, inter‐annual and extreme rainfall over the NWH region. Based on the comprehensive analysis of global and regional models, it is noted that the CMIP5‐MMM has better ability to simulate rainfall pattern during monsoon season compared with the finer resolution CORDEX‐MMM for both the states of UK and HP. Therefore, it is suggested that CMIP5 models may be utilized to investigate the rainfall variability at daily, seasonal and interannual scales over the NWH region for various forcing scenarios rather than the outputs from CORDEX‐SA domain. Abstract : Spatial map for mean monsoon rainfall (in mm day −1 ) using (a) IMD gridded rainfall data, (b) CORDEX‐MMM rainfall and (c) CORDEX‐MMM minus CMIP5‐MMM rainfall during 1976–2000 over NWH region. Analysis of CMIP5 and CORDEX‐SA models conducted for the monsoon season rainfall. Assessment of the model derived results is done w.r.t. the IMD data sets. CMIP5 performs better than CODEX‐SA over the NWH region.